Development of sensor and data collection system for power substation monitoring - Lee, Jordan Yong Ming (2017)
Since the demand for quality electricity grows, there is the need to be able to keep up with the expectations of being a good power utility in Singapore. Therefore transmission and distribution equipment have to be properly maintained to be able to keep up with the standards. The process of condition monitoring can be slightly automated and be safer with the help of non-intrusive measurement instruments such as thermal imaging processing.